Pinchbeck regulars? The role and organisation of the Territorial Army, 1919-1940. - Jones, A (2016)
This thesis examines how Britain’s government and military establishment conceptualised the role of the voluntary Territorial Army (TA) between the World Wars, and explores the relationship with British defence policy during the period. It also evaluates whether or not the TA was capable of carrying out its ascribed role, through a balanced assessment of its organisation, training and military efficiency. It posits that the TA was integral to British defence planning and played a key part in the Army’s mobilisation plans, although the priority given to its role shifted throughout the period in accordance with the direction of Britain’s strategic focus. Additionally, this thesis will emphasise that the Territorial Army had not one purpose but several. Alongside its central function as the framework for a conscript National Army it held key responsibilities for both home and imperial defence. This thesis examines the TA’s role and organisation in a thematic and broadly chronological manner. Part I deals with the TA’s expeditionary role and its function as the framework for all future military expansion, as well as its role as a voluntary imperial reserve for any medium scale wars conducted without resorting to conscription. Part II focuses on the Territorial Army’s home defence responsibilities, in particular its domestic role in aiding the civil power and its contribution to Britain’s increasingly important air defence capabilities.